In the House of Heqanakht : Text and Context in Ancient Egypt. Studies in Honor of James P. Allen - Almansa-Villatoro, M. Victoria, (Harvard Egyptological Studies ;, 2023)
In the House of Heqanakht: Text and Context in Ancient Egypt gathers Egyptological articles in honor of James P. Allen, Charles Edwin Wilbour Professor of Egyptology at Brown University. Professor Allen's contribution to our current understanding of the ancient Egyptian language, religion, society, and history is immeasurable and has earned him the respect of generations of scholars. In accordance with Professor Allen's own academic prolificity, the present volume represents an assemblage of studies that range among different methodologies, objects of study, and time periods. The contributors specifically focus on the interconnectedness of text and context in ancient Egypt, exploring how a symbiosis of linguistics, philology, archaeology, and history can help us reconstruct a more accurate picture of ancient Egypt and its people. The Figshare images in this volume have been made available online and can be accessed at https://figshare.com/s/8b3e5ad9f8a374885949